Phenotypic memory in Bacillus subtilis links dormancy entry and exit by a spore quantity-quality tradeoff - Mutlu, Alper; Nagler, Katja; Bergeest, Jan-Philip; Rohr, Karl; Bischofs-Pfeifer, Ilka (Nature Communications, 2018)
Bacillus subtilis withstands starvation by forming dormant spores that revive when nutrients become available. Here, Mutlu et al. show that sporulation timing controls spore revival through a phenotypic ‘memory’ that arises from the carry-over of a metabolic enzyme from the vegetative cell into the spore.